Kenya Climate-Smart Agriculture program validation workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This validation workshop brought together stakeholders to look through Kenya's Climate-Smart Agriculture program result areas. Photo: V. Atakos (CCAFS)